Exploring the Intersections of Science and History Learning. (2nd July 2016) - Hughes, Catherine; Cosbey, Allison
ABSTRACT: How can history museums incorporate Science, Technology, Engineering and Math (STEM) activities while preserving their missions and identities? How do interdisciplinary experiences lead to learning? A cross-institutional exhibit development and evaluation team wrestled with these ideas as they developed Create.Connect, an National Science Foundation-funded exhibition at Conner Prairie designed to weave together historical narrative and STEM activity. The goal was to create a truly interdisciplinary experience, where history and STEM learning would not just exist side-by-side, but interact in ways that might spark new interest or deeper learning. While visitors to Conner Prairie accepted, enjoyed and valued the Create.Connect experience, and families explored both history and STEM during their visit, conceptualizing and defining "integrated" history and STEM learning proved challenging for both exhibit developers and evaluators. What emerged were several definitions and levels of integration and a nascent understanding of the complexity of learning in interdisciplinary exhibitions.